2014
DOI: 10.1111/jcal.12048
|View full text |Cite
|
Sign up to set email alerts
|

System, scholar or students? Which most influences online MBA course effectiveness?

Abstract: Considering the increasingly challenging resource environments in many business schools, this study examined whether course technologies, learner behaviors or instructor behaviors best predict online course outcomes so that administrators and support personnel can prioritize their efforts and investments. Based on reviewing prior online and blended management education literature, we hypothesized that instructor behaviors would be most predictive of online course outcomes. However, our study of 48 online Maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 78 publications
(136 reference statements)
4
89
0
1
Order By: Relevance
“…While an increasing body of research is becoming available how students' usage and behaviour in LMS influences academic performance (e.g., Arbaugh, 2014;Macfadyen & Dawson, 2010;Marks et al, 2005;Wolff et al, 2013), how the use of e-tutorials or other formats of blended learning effects performance (e.g., Lajoie & Azevedo, 2006), and how feedback based on learning dispositions stimulates learning (Buckingham Shum and Deakin Crick (2012), to the best of our knowledge no study has looked at how all these factors can be combined into one research context, and what the relative contributions of LMSs, formative testing, e-tutorials, and applying dispositional learning analytics to student performance are. In our empirical contribution focusing on a large scale module in introductory mathematics and statistics followed by 922 students, we aim to provide a practical application of such an infrastructure based on combining longitudinal learning data from our LMS, the two e-tutorials, and (self-reported) learner data.…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While an increasing body of research is becoming available how students' usage and behaviour in LMS influences academic performance (e.g., Arbaugh, 2014;Macfadyen & Dawson, 2010;Marks et al, 2005;Wolff et al, 2013), how the use of e-tutorials or other formats of blended learning effects performance (e.g., Lajoie & Azevedo, 2006), and how feedback based on learning dispositions stimulates learning (Buckingham Shum and Deakin Crick (2012), to the best of our knowledge no study has looked at how all these factors can be combined into one research context, and what the relative contributions of LMSs, formative testing, e-tutorials, and applying dispositional learning analytics to student performance are. In our empirical contribution focusing on a large scale module in introductory mathematics and statistics followed by 922 students, we aim to provide a practical application of such an infrastructure based on combining longitudinal learning data from our LMS, the two e-tutorials, and (self-reported) learner data.…”
Section: Research Questionsmentioning
confidence: 99%
“…User behaviour data are frequently supplemented with background data retrieved from learning management systems (LMS) (Macfadyen & Dawson, 2010) and other student admission systems, such as accounts of prior education (Arbaugh, 2014;Richardson, 2012). For example, in one of the first learning analytics studies focused on 118 biology students, Macfadyen and Dawson (2010) found that some (# of discussion messages posted, # assessments finished, # mail messages sent) LMS variables but not all (e.g., time spent in the LMS) were useful predictors of student retention and academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of elearning, TAM could not only be used for predicting adoption behavior, but also for measuring the learning satisfaction, continuous intention to use e-learning (Pereira, Ramos, Gouvêa, & Costa, 2015), loyalty to elearning (Sánchez-Franco, Peral-Peral, & Villarejo-Ramos, 2014), course outcomes, and academic performance using e-learning (Arbaugh, 2014). The features of technology: interactivity, personalisation, accessibility, mobility, and the choice of media to present the contents (Agudo-Peregrina, Hernández-García, & Pascual-Miguel, 2014); individual characteristics such as personal innovativeness in information technology, computer self-efficacy, and demographic variables (Chow et al, 2013;Thatcher & Perrewe, 2002);the course characteristics of learning resources, course content, tutor quality, and course quality (Persico, Manca, & Pozzi, 2014;Teo, 2014); and other variables such as social influence (or social norm) and flow (Wu & Zhang, 2014), are incorporated into TAM to enhance the understanding of adopting.…”
Section: Theoretical Background Technology Acceptance Modelmentioning
confidence: 99%
“…A previous study [1] has focussed on learner engagement in the context of online management programmes. This study of 48 online MBA courses, from one institution, investigated the impact of course technologies, instructor behaviours and learner behaviours on perceived learning, learner performance and learner satisfaction.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, because Imperial's in-house LMS has been co-developed and evaluated with students, tutors and administrators over a number of years, acceptance of this technology by these cohorts of students is also not a primary issue in our context (c.f. [1]). However, there is still variability in students' performance and their levels of satisfaction with their courses.…”
Section: Related Workmentioning
confidence: 99%